GCMS BASED METABOLIC PROFILING OF ESSENTIAL OIL OF CITRUS MACROPTERA MONTRUZ. LEAVES AND PEEL, ASSESSMENT OF IN VITROANTIOXIDANT AND ANTI-INFLAMMATORY ACTIVITY - Khumukcham, Nongalleima; Ajungla, T.; Singh, Chingakham Brajakishore (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: The present investigation was designed for Gas Chromatography Mass Spectrometry (GCMS) based metabolite profiling of Citrus macroptera Montruz. Leaves and peel oils followed by assessment of in vitro antioxidant and anti-inflammatory activity. Methods: Essential oil was extracted from leaves and peels of Citrus macroptera Montruz. The oil samples were subjected to GCMS analysis using Shimadzu GCMS-QP2010 equiped with an AOC-2oi auto-injector and AOC-2os autosampler units. In vitro antioxidant activities were evaluated using DPPH radical scavenging, reducing power and nitric oxide reducing method. In vitro anti-inflammatory activity was evaluated using protease inhibitory assay, heat induced haemolysis and albumin denaturation assay. Results: Both the peels and leaves of Citrus macroptera Montruz. Yielded good amount of essential oil. 57 compounds each were identified from leaves as well as peel of C. macroptera. 10 common compounds have been detected in both the oil samples. Peels oil showed IC50 at 118.07 µg/ml and that of leaves showed IC50 at 252.93 µg/ml in DPPH (1, 1-diphenyl-2-picrylhydrazyl) assay. In reducing assay, peel and leaves oil showed IC50 at 122.5 µg/ml and 208.24 µg/ml. In albumin denaturation, the peels showed IC50 at 73.91 µg/ml and that of leaves showed IC50 at 87.48 µg/ml. Conclusion: The oil yield denotes peel as better source of volatile oil than leaves. Essential oil of peel showed more anti-oxidant and anti-inflammatory activity than that of leaves essential oil.